Water Quality Status of Historical Antiya Tall at Jhansi City as a Primary Data for Sustainable Approach - Sonkar1, Minakshi2, Anshu Dhaka3; Chanchal1, Vinit Kumar1, Sandeep Arya1*, Preeti (Recent Research in Science and Technology, 2011)
Lakes are sometime subjected to waste water discharges originating from different sources. Antiya Tall is an urban water body, surrounded by residential area receiving municipal waste water, sewage and solid waste from Jhansi City. A total of eighteen samples were collected since January 2010-Jun2010 from three sites of Antiya Tall to analyze the twelve physico-chemical parameters and four heavy metals. The overall average values of these physico chemical parameters during the study period were observed as temperature (24.8+6.070C), pH (8.35+0.94), turbidity (47.78+11.34 NTU), total dissolved solid (940.39+147.27 mg/l), dissolved oxygen (2.20+0.79 mg/l), biochemical oxygen demand (7.12+1.62 mg/l), chemical oxygen demand (42.10+14.59 mg/l), alkalinity (386.50+81.31 mg/l), total hardness (552.50+74.94 mg/l), chloride (53.66+20.04 mg/l), fluoride (1.79+0.66 mg/l), nitrate (21.89+5.43 mg/l), lead (0.51+0.19 mg/l), cadmium (0.39+0.13 mg/l), iron (3.98+0.60 mg/l) and chromium (1.02+0.23 mg/l). The physico chemical parameters represent significant correlation with seasonal variation and heavy metals are found in slightly higher concentration than their permissible limits.